2021
DOI: 10.1021/acs.cgd.1c00101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Volume on the Nucleation of Model Organic Molecular Crystals through an Induction Time Approach

Abstract: Analysis of the probability distribution of induction times for acetaminophen and glycine supersaturated solutions showed that reduction in sample volume results in an exponential increase in induction times. It approximately increased by a factor of 55 when the volume was reduced from 1000 to 25 μL. To elucidate the use of confinement as an approach to nanocrystal development and polymorph access, we demonstrated the effect of volume reduction on the nucleation of two model compounds, acetaminophen and glycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…For TEM measurements, the samples are prepared by dropping 2.0 μL onto a 300 mesh copper grid coated with carbon. The grids were blotted on filter paper to avoid artifacts. , The induction time (τ) of nucleation was determined via the increasing turbidity of the solution and the appearance of the first crystal in a solution as detected by optical microscopy (AmScope 40X-2500X) …”
Section: Methodsmentioning
confidence: 99%
“…For TEM measurements, the samples are prepared by dropping 2.0 μL onto a 300 mesh copper grid coated with carbon. The grids were blotted on filter paper to avoid artifacts. , The induction time (τ) of nucleation was determined via the increasing turbidity of the solution and the appearance of the first crystal in a solution as detected by optical microscopy (AmScope 40X-2500X) …”
Section: Methodsmentioning
confidence: 99%
“…Crystallization is a crucial unit operation in the pharmaceutical, food, and chemical industries that allows the generation of specialized solid materials with desired attributes such as purity, polymorphism, size distribution, and morphology. Crystal morphology is one of the most important property indicators of pharmaceutical solids, as it could influence the performances of the products and subsequent downstream processing. For example, needle-like crystals with a high aspect ratio raise difficulties in the blending stage and tableting process due to the poor flowability, tend to clog the equipment, and break easily. Flake-shaped crystals result in poor efficiency in filtering and washing since they tend to pack as an impermeable layer on the filter media.…”
Section: Introductionmentioning
confidence: 99%
“…These authors observed a very strong increase of the nucleation rate in moving compared to static droplets, while somewhat lower nucleation rates were found in the stirred vials, despite a two orders of magnitude higher shear rate in the stirred vials. On a separate note, Dela Cruz et al concluded that changes in the shape of the probability distribution is an indication of the change in the nucleation regimes, which in most cases is caused by polymorphism, i.e., because of concomitant nucleation of two polymorphic forms or by transformation of a metastable into a more stable polymorph. A more extensive review of microfluidic induction time measurements can be found in following review articles. ,, …”
Section: Introductionmentioning
confidence: 99%